Beyond Stereotypes : American Jews and Sports in the Twentieth Century - Ansell, Lisa; Sclar, Ari F; Zuckerman, Bruce (Jewish role in American life, 2015)
In the decades after the Civil War, sports slowly gained a prominent position within American culture. This development provided Jews with opportunities to participate in one of the few American cultures not closed off to them. Jewish athleticism challenged anti-Semitic depictions of Jews' supposed physical inferiority and an Americanization narrative emerged that connected Jewish athleticism with full acceptance and integration into American society. This acceptance was not without struggle, but Jews succeeded and participated in the American sporting culture as athletes, coaches, owners, and fans. The contributions to this volume paint a broad picture of Jewish participation in sports, with essays written by respected historians who examine the impact of sport on Judaism. Despite the continued belief that Jewish religious or cultural identity remains somehow distinct from the American idea of the "athlete," the volume demonstrates that American Jews have made a tremendous contribution to American sports, and that sports have helped construct American Jewish culture and identity.